2011
DOI: 10.1063/1.3551543
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic metastability of orthorhombic HfTiO4 in thin film hafnia-titania

Abstract: Orthorhombic (o) HfTiO4 is crystallized when sputter deposited hafnia-titania nanolaminates with ultrathin layers and bilayer (HfO2)0.5(TiO2)0.5 composition are annealed between 573 and 1173 K. However, o-HfTiO4 demixes after annealing at 1273 K, a result not predicted from bulk thermodynamics. X-ray diffraction and Raman microscopy are used here to study structural changes as o-HfTiO4 demixes upon long-term annealing at 1273 K into Ti-doped monoclinic HfO2 and Hf-doped rutile TiO2. We conclude that o-HfTiO4 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…1,3 The aforementioned double peak vicinal to the rutile standard, labeled A and B, as well as a lower angle peak, labeled C, were also observed after 24 h at 1273 K. Peak A is attributed to the (110) planes of TiO 2 :Hf as before, 1-3 but peak B is now attributed to hafnon (200) planes. 8 Peak C is attributed to hafnon (101) planes.…”
mentioning
confidence: 77%
See 3 more Smart Citations
“…1,3 The aforementioned double peak vicinal to the rutile standard, labeled A and B, as well as a lower angle peak, labeled C, were also observed after 24 h at 1273 K. Peak A is attributed to the (110) planes of TiO 2 :Hf as before, 1-3 but peak B is now attributed to hafnon (200) planes. 8 Peak C is attributed to hafnon (101) planes.…”
mentioning
confidence: 77%
“…Post-deposition air annealing was carried out first at 1173 K for up to 192 h (denoted stage I). Previous results on the same architecture 1 showed that annealing at 1173 K for 1 h did not produce a double XRD peak vicinal to (110) rutile. Here, we wanted to determine whether long term annealing at 1173 K would produce it.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…We previously reported that orthorhombic (o) HfTiO 4 in sputter deposited films on fused SiO 2 substrates demixes upon annealing to form monoclinic (m) HfO 2 and rutile (r) TiO 2 . 6,7 When demixing occurs at high temperature (1273 K), crystalline hafnon (HfSiO 4 ) with a zircon archetype lattice is formed, 8 indicating a reaction between the film and the substrate. This last result is surprising because HfSiO 4 does not form in a HfO 2 -on-SiO 2 film subjected to a similar annealing regimen.…”
mentioning
confidence: 99%